PERANAN ANGGOTA KELOMPOK TANI DALAM MENINGKATKAN PRODUKTIVITAS USAHA TANI TANAMAN SAWI DI DESA NETPALA KECAMATAN MOLLO UTARA KABUPATEN TIMOR TENGAH SELATAN - Febi Neonleni; Ernantje Hendrik; Lika Bernadina; Satria Putra Utama (Buletin Ilmiah Impas, 2021)
This research was conducted in Netpala Village, North Mollo District, South Central Timor Regency, with the aim of knowing the role of farmer group members and the factors related to the role of farmer group members in increasing mustard plant productivity. The research method used is a survey method. The sample was randomly selected as many as 54 members of the farmer group. Analysis of the data used is a non-parametric statistical test Spearman Rank Correlation. The results showed that 1) The role of farmer group members in increasing the productivity of mustard plant farming was in the frequent category with a value of 75.8%. The element that contributed the most was the role in implementing the farmer group activity plan of 76.9% with an average score of 124.60. The element that contributed the least to the role of farmer group members was the role in applying mustard farming technology by 51.1% with an average score of 82.8, and 2) Factors related to the role of farmer group members in increasing the productivity of mustard farming were land area with a correlation coefficient value (rs) of 0.685 was unidirectional. The relationship between the two variables was strong with the value of t count > t table (7.213> 1.666). This means that the wider the cultivated area, the higher the productivity of mustard farming. The factor that has the smallest significant relationship for the role of farmer group members was the experience of farming with a coefficient value (rs) of 0.413 which was at the level of sufficient correlation with t count 3.271 > t table 1.666. While the factor of formal education there was no real relationship with the role of members of farmer groups